Penggunaan Citra Aster Dalam Identifikasi Peruntukan Lahan Pada Sub Das Lesti (Kabupaten Malang) - Wibowo, Leo Arbi; Sholichin, Mohammad; Rispiningtati, Rispiningtati; Asmaranto, Runi (Fakultas Teknik, Universitas Brawijaya, 2013)
The indicator impaired balance the hydrologic cycle in watershed was characterized by the number of occurrences of floods, landslides, droughts and pollution of water quality. Lesti sub-watershed was part watershed Brantas contained in the upstream sub-watershed is a priority and having problems against land degradation, erosion and landslides. A lot of effort can be done in order to restore the balance of the hydrological cycle in the watershed so that the quality and quantity of water resources are maintained, one of the efforts that can be done is by way of determination of critical areas which will be used as a reference for determining priority areas for the handling. This effort while increasing productivity, income and socio-economic conditions of the people in the uplands. In determining the criticality of land and conservation directives Lesti sub-watershed, needed some supporting data, one of the most important data is the data of land use. To get land use map in the sub-watershed Lesti, one way that can be used is to perform image interpretation ASTER (Advanced Spaceborne Thermal Emission and Reflection Radiometer) obtained from TERRA satellite. The use of ASTER imagery in the identification of land use is feasible by using sub-system VNIR (Visible and Near-Infrared Radiometer), which has a spatial resolution up to 15 meters above the ground.Key words: Topography map, Watershed, ASTER image, Classification, Land Use Map.